The Evaluation of Coramil Model Program in KODIM (District Military Command) 1207/BS at Pontianak City - Edy Kuswanto; M. Chiar; Sukmawati Sukmawati (JETL (Journal of Education, Teaching and Learning), 2019)
The Koramil Model program that is formed at this time, especially those in the Kodim 1207/BS Pontianak ranks has not yet described the expected results in accordance with the objectives of the establishment of the Koramil Model. This study aims to improve the quality of Apkowil through an evaluation of the Koramil Model program at Kodim 1207/BS Pontianak. This type of research is evaluative research. The program evaluation procedure for the Koramil Model in Kodim 1207/BS Pontianak in this study uses evaluation of the CIPP model (Context, Input, Process, and Product). The results of this study indicate that (1) the results of the context evaluation of the Koramil Model program at Kodim 1207/BS Pontianak containing program planning fall into less criteria; (2) the results of the evaluation of inputs (input) of the Koramil Model Program in Kodim 1207/BS Pontianak are included in the criteria of very few; (3) the results of the evaluation of the Koramil Model program implementation process at the Kodim 1207/BS Pontianak included in the criteria were not appropriate; (4) the results of the evaluation of the Koramil Model program at the Kodim 1207/BS Pontianak included in the criteria of lacking.